THE MAIN ROLE OF BACTERIA IN THE CHEMOTAXIS PROCESS - Rozimova H. K. (Galaxy International Interdisciplinary Research Journal, 2022)
There is a process in microbiology - chemotaxis. This means that microorganisms move towards organic compounds. Plant roots are rich in such compounds. Naturally, soil microorganisms move towards the root and start living in the root. They are interested in the long life of the plant. Therefore, it supplies all the necessary compounds for the plant.